Glenn Gould : the ecstasy and tragedy of genius - Ostwald, Peter F. 4 0 16; 5 (New York : W.W. Norton, 1997)
The Canadian pianist Glenn Gould was a musical genius - a child prodigy whose rise to world fame was jump-started in 1955 by a sensational recording of Bach's daunting Goldberg Variations. As his career continued to blossom, Gould made his mark as a world-renowned pianist, composer, and conductor but also demonstrated his talent and intelligence as an influential critic, essayist, philosopher, actor, comedian, and filmmaker. But along with his charm, Gould was tragically disturbed - a recluse with nocturnal work habits, obsessed by physical and mental complaints, he relied heavily on prescription drugs. He consulted scores of doctors, avoided intimacy, and never married. Struggling against lifelong physiological and psychological problems that always threatened to overwhelm him, Gould neglected his health and died prematurely at age fifty of a massive stroke. Glenn Gould's life raises many questions about the phenomenon of genius. Was Gould's genius sponsored by his eccentricity or vice versa? Do men and women of genius sacrifice themselves in the service of a higher ideal while remaining personally unfulfilled? Dr. Peter Ostwald, a professor of psychiatry noted for his expertise in psychobiography and a skilled violinist who played chamber music with Gould, captures the brilliant fusion of genius and eccentricity that composed this highly mysterious and appealing figure.
1 The Concert 17 -- 2 A Little Night Music 25 -- 3 Infancy 35 -- 4 Child Prodigy 43 -- 5 A Childhood Friend 57 -- 6 New Teachers and Further Success 67 -- 7 Gaining a Manager 81 -- 8 My Love Affair with the Microphone 89 -- 9 Self-Isolation 98 -- 10 Triumph in the States 110 -- 11 First Contact with Psychiatry 120 -- 12 Conflicting Demands 130 -- 13 Telephone Calls 142 -- 14 Traveling Overseas 149 -- 15 Strange Illnesses 159 -- 16 In Search of a Home 171 -- 17 Dr. Joseph Stephens 185 -- 18 The Pitfalls of Composing and Performing 200 -- 19 Retirement from the Stage 214 -- 20 The Solitude Trilogy 230 -- 21 Changing Views of Composers 244 -- 22 Impersonator, Philosopher, and Technician 258 -- 23 New Faces, New Challenges 271 -- 24 Approaching Middle Age 286 -- 25 The Last Years 304 -- 26 A Fatal Stroke 320
Includes bibliographical references and index
Keywords: 2 -- 0; 6; 20; 20; 2